The influence of high glucose conditions on macrophages and its effect on the autophagy pathway - Sousa, Emanuella S. A.; Queiroz, Luiz A. D.; Guimarães, João P. T.; Pantoja, Kamilla C.; Barros, Rafael S.; Epiphanio, Sabrina; Martins, Joilson O. (Frontiers in Immunology, 2023)
Introduction Macrophages are central cells in mediating the inflammatory response. Objective and Methods We evaluated the effect of high glucose conditions on the inflammatory profile and the autophagy pathway in Bone-Marrow Derived Macrophages (BMDM) from diabetic (D-BMDM) (alloxan: 60mg/kg, i.v.) and non-diabetic (ND-BMDM) C57BL/6 mice. BMDM were cultured in medium with normal glucose (5.5 mM), or high glucose (25 mM) concentration and were primed with Nigericin (20µM) stimulated with LPS (100 ng/mL) at times of 30 minutes; 2; 4; 6 and 24 hours, with the measurement of IL-6, IL-1β and TNF-α cytokines. Results We have further identified changes in the secretion of pro-inflammatory cytokines IL-6, IL-1β and TNF-α, where BMDM showed increased secretion of these cytokines after LPS + Nigericin stimulation. In addition, changes were observed in the autophagy pathway, where the increase in the autophagic protein LC3b and Beclin-1 occurred by macrophages of non-diabetic animals in hyperglycemic medium, without LPS stimulation. D-BMDM showed a reduction on the expression of LC3b and Beclin-1, suggesting an impaired autophagic process in these cells. Conclusion The results suggest that hyperglycemia alters the inflammatory pathways in macrophages stimulated by LPS, playing an important role in the inflammatory response of diabetic individuals.